2021
DOI: 10.3390/ijms22115881
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Serotonin Biosynthesis and Its Functional Role in L-Arginine-Induced Gastric Proton Secretion

Abstract: Among mammals, serotonin is predominantly found in the gastrointestinal tract, where it has been shown to participate in pathway-regulating satiation. For the stomach, vascular serotonin release induced by gastric distension is thought to chiefly contribute to satiation after food intake. However, little information is available on the capability of gastric cells to synthesize, release and respond to serotonin by functional changes of mechanisms regulating gastric acid secretion. We investigated whether human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…For all five selected peptides, a significant hormetic concentration-dependent influence on the secretory activity was found. Holik et al showed a hormetic dose–response when HGT-1 cells were incubated with l -arginine. HGT-1 cells released more serotonin when treated with lower l -arginine concentrations (10 mM) than with higher l -arginine concentrations (50 mM).…”
Section: Resultsmentioning
confidence: 99%
“…For all five selected peptides, a significant hormetic concentration-dependent influence on the secretory activity was found. Holik et al showed a hormetic dose–response when HGT-1 cells were incubated with l -arginine. HGT-1 cells released more serotonin when treated with lower l -arginine concentrations (10 mM) than with higher l -arginine concentrations (50 mM).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were expanded and fully differentiated as previously described 22 . The human gastric tumor cell line HGT‐1 was cultured as described earlier 23 …”
Section: Methodsmentioning
confidence: 99%
“…Proton secretory activity and corresponding data analysis were conducted by means of the pH‐sensitive fluorescence dye 1,5 carboxy‐seminaphto‐rhodafluor acetoxymethylester (SNARF‐1‐AM; Life Technologies), as described previously 23 …”
Section: Methodsmentioning
confidence: 99%
“…The impact of the evaluated compounds on cell viability was assessed using the tetrazole MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) reagent. Cells were cultivated in a 96-well plate at a density of 10,000–100,000 viable cells per well and settled for 24–72 h. The assay was applied as previously explained [ 20 ]. Cell viability was determined relative to medium-only treated control cells (untreated controls = 100%).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, high signal-to-noise ratios and the need to precisely control external CO 2 levels in order to prevent long time alkalization of the extracellular pH have been observed, particularly when using the standard extracellular medium DMEM which relies on the HCO 3 − /CO 2 buffer system for regulating extracellular pH. In one of our recent works, we used KREBS-Ringer HEPES buffer instead of the cell culture medium DMEM [ 17 ] in order to directly compare results from a serotonin-release assay with those of the proton secretion assay in HGT-1 cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%